EFEKTIVITAS METODE INQUIRY LEARNING TERHADAP HASIL BELAJAR IPA PADA TEMA ENERGI DAN PERUBAHANNYA - Imroatik Zahrotul Khoiriyah; Silviana Nur Faizah; Minahul Mubin (Universitas Islam Lamongan, 2019)
Learning method is a way that is taken or used by the teacher to deliver a learning material in an effort to achieve the goals of a learning. Whereas lPA is one of the lessons that must involve students directly with the implementation of practicums to improve students' skills. In the process of learning science at SDN Tlogoagung, researchers found that learning outcomes were still low, the average score was 60% lower than the specified KKM, which was 75. This was possible because of the conventional learning process. The focus of the research that will be discussed in this study is about how the effectiveness of the inquiry learning method for learning outcomes and the skills of the science learning process in the matter of energy and its changes. The purpose of this study was to determine the effectiveness of the method of inquiry learning on learning outcomes and the skills of the science learning process on energy matter and its changes. The method used in this study is an experimental method using nonequivalent control group design. Data collection techniques used were interviews, tests, observation sheets and documentation. While the data analysis used is the validity test, reliability test, normality test, homogeneity test, assessment of the test, mean, achievement of learning outcomes, N-Gain, observation of basic process skills, and hypothesis testing using Independent samples t-test. From the results of the study it is known that the use of inquiry learning methods seen from the results of learning between the experimental class with the control class, while the average value of the experimental class post test is 87 while the average value of the control class post test is 79. Based on the results of hypothesis testing indicates that the value sig (2 tailed) smaller than 0.05 so Ho is rejected and Ha is accepted. This means that the inquiry learning method is effective on learning outcomes and the skills of the science learning process on energy matter and its changes.